The Effect of Baby Massage Stimulation Learning E-Module on The Skills of Students in D-III Midwifery - Sitti Nurjannah; Andi Agussalim; Elizabet C Jusuf; Martira Maddeppungeng; Sharvianty Arifuddin; Andi Nilawati Usman (Poltekkes Kemenkes Palu, 2023)
Baby massage offers many benefits, especially for the growth and development of babies. Baby massage skills are very important in supporting the success of stimulating the baby's growth and development. Therefore, it is very important to improve the skills of midwifery students. One of the efforts to improve the skills is providing web-based e-modules on infant massage stimulation learning. This research aims to determine the effect of infant massage stimulation learning e-module on the skills of DIII midwifery students. The research employed the quasi-experiment. The sampling technique was total sampling. The sample included 76 midwifery students in semester 4. The study was conducted in two locations. The intervention group comprised 36 students and the control group consisted of 40 students. Using McNemar and Mann Whitney, the research found that there was a significant effect baby massage stimulation pre test and posttest skills (p-values 0.00<0.05) and ther is also a significant effect on the comparison of baby massage stimulation skills between the intervention and control groups (p-values 0.00<0.05). The conclusion is there is an effect of the use of e-modules on increasing the skills of DIII midwifery student.